2019
DOI: 10.1016/j.ecosys.2018.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Long-term finance and entrepreneurship

Abstract: This paper investigates whether long-term finance affects the firm entry across the world. We construct a new database on short-term and long-term credit provided by commercial banks to the private sector in 85 countries over the period 1995-2014. We then analyze whether differences in entrepreneurship are correlated with the provision of short-term and long-term bank credit. Data on entrepreneurship are extracted from two frequently used databases: the Global Entrepreneurship Monitoring dataset and Entreprene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 61 publications
1
15
0
1
Order By: Relevance
“…However, there are important things that the university has been providing long-term capital in entrepreneurship development for students (Erikson, 2002). The various efforts made by universities, which cover various fields of university activity in the form of academic initiatives, and creation of innovation centers, commercialization of research results, expansion of funding sources, promotion of entrepreneurial culture and good business environment, and active cooperation with business community members (Léon, 2019;Genoveva, 2019;Guerrero & Urbano, 2012). Such programs are actually trying to change students' mindset from being employee become an independent entrepreneur.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are important things that the university has been providing long-term capital in entrepreneurship development for students (Erikson, 2002). The various efforts made by universities, which cover various fields of university activity in the form of academic initiatives, and creation of innovation centers, commercialization of research results, expansion of funding sources, promotion of entrepreneurial culture and good business environment, and active cooperation with business community members (Léon, 2019;Genoveva, 2019;Guerrero & Urbano, 2012). Such programs are actually trying to change students' mindset from being employee become an independent entrepreneur.…”
Section: Discussionmentioning
confidence: 99%
“…A significant proportion of studies, however, found an insignificant link between LTC and firm growth. A reasonable explanation is that LTC isn't crucial for daily operations, as working capital requirements of small and young firms is markedly important (Field, Pande, Papp, & Rigol, 2013;Getachew, 2016;Lay, 2020;Leon, 2018;Leon, 2019). Studies by Fisman and Love (2007) and Fafchamps and Schündeln (2013) studied the impact of growth opportunities by including it in the base model and analyzing its relationship with credit growth maturity.…”
Section: Discussionmentioning
confidence: 99%
“…Andrade, Cahn, Fraisse, and Mésonnier (2019) recommended that, in order to address any gaps or shortcomings in a firm's performance (FP), some contextual factors and variables like LTC and STC, which affect the quality of a firm, need to be identified and evaluated in detail. Research on the impact of the growth of employment (GoE) on FP is limited, so studies needs to be conducted on firms and businesses in different developing regions and countries (Leon, 2019). As of yet, no studies have evaluated the direct impact of GoE on LTC and STC performance; therefore, this research is new and justified in understanding the direct influence of GoE and sales of total sales (STS).…”
Section: Background Of the Studymentioning
confidence: 99%
“…Many scholars have studied entrepreneurial development depending on the business environment to increase the number of entrepreneurs and the rate of business growth ( Sattari and Mehrabi, 2016 ; Khan et al, 2019 ; Radović-Marković et al, 2019 ; Jang et al, 2020 ). Other researchers have explored the positive effects of financial development on promoting entrepreneurship ( Civera et al, 2017 ; Léon, 2019 ; Hommel and Bican, 2020 ; Liu et al, 2020 ; Srivastava et al, 2021 ; Charfeddine and Zaouali, 2022 ). In addition, the development of innovation has contributed significantly to entrepreneurship and economic growth ( Huggins and Thompson, 2015 ; Ferreira et al, 2017 ; Pounder, 2019 ; Pradhan et al, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%